Coherent Radio Emission from “Main-sequence Radio Pulse Emitters”: A New Stellar Diagnostic to Probe 3D Magnetospheric Structures - Barnali Das; Poonam Chandra; Véronique Petit (The Astrophysical Journal)
Main-sequence radio pulse emitters (MRPs) are magnetic early-type stars that produce coherent radio emission observed in the form of periodic radio pulses. The emission mechanism behind this is the electron-cyclotron maser emission (ECME). Among all kinds of magnetospheric emission, ECME is unique due to its high directivity and intrinsically narrow bandwidth. The emission is also highly circularly polarized and the sign of polarization is opposite for the two magnetic hemispheres. This combination of properties makes ECME highly sensitive to the three-dimensional structures in the stellar magnetospheres. This is especially significant for late-B and A-type magnetic stars that do not emit other types of magnetospheric emission such as H α , the key probe used to trace magnetospheric densities. In this paper, we use an ultra-wideband observation (0.4–2 GHz) of a late B-type MRP HD 133880 to demonstrate how we can extract information on plasma distribution from ECME. We achieve this by examining the differences in pulse arrival times (“lags”) as a function of frequencies and qualitatively comparing those with lags obtained by simulating ECME ray paths in hot stars’ magnetospheres. This reveals that the stellar magnetosphere has a disk-like overdensity inclined to the magnetic equator with a centrally concentrated density that primarily affects the intermediate frequencies (400–800 MHz). This result, which is consistent with the recent density model proposed for hotter centrifugally supported magnetospheres, lends support to the idea of a unifying model for magnetospheric operations in early-type stars, and also provides further motivation to fully characterize the ECME phenomenon in large-scale stellar magnetospheres.